ARTISTIC RESEARCH: THE THOUGHTS AND IDEAS OF MIKA HANNULA - Guntur Guntur (ARTISTIC : International Journal of Creation and Innovation, 2020)
This paper is a review of the thoughts and ideas of Mika Hannula presented in his book Artistic Research: Theories, Methods, and Practices. As its title indicates, this book discusses artistic research, specifically related to the theories, methods, and practices of its implementation. In this paper the writer attempts to review: the urgency of artistic research, the philosophical foundations of artistic research, artistic research and science, epistemology and axiology, methodology of artistic research, and its expediency and guidelines for use in art research.